Molecular characterization, body parameters and management practices of Purnea cattle - SHARMA, REKHA; SINGH, P K; MAITRA, A; PANDEY, A K; MUKESH, M; SINGH, S R; SINGH, BIRENDER (The Indian Journal of Animal Sciences, 2013)
The present study is our contribution to the ongoing national endeavor of characterizing indigenous livestock geneticresources. The phenotypic parameters, management practices and genetic variability status of Purnea cattle were evaluated. A survey was conducted in different villages of Purnia commissionary of Bihar. These animals were kept under zero or very low input system of management. The animals were of small size and compact body. The coat   colour of Purnea cattle ranged from light to deep red with   few grayish white animals. The body length, chest girth, height   at withers, paunch girth, face length, tail length    with and without switch, horn length and ear length were measured in 205 animals belonging to different age/ sex groups. Purnea is  the smallest cattle in Bihar based on morphometric measurements. The head profile was straight in females and slightly budged in males. The colour of   eyelid, muzzle and tail switch were mostly black. The horns were short, set in a crescent shape and point forward. The udders were small in size and bowl in shape. The age at sexual maturity in males was about 2.5 to 3.0 years and age at first calving of cows was between 3 and 4 years of age. The average daily milk yield of cows was 0.5 to 2.0 kg. Genotyping was done with 23 bovine microsatellite markers as suggested by International Society for Animal Genetics (ISAG) and FAO (DAD-IS) on automated sequencer. A total  of 204 alleles were observed. The mean number of observed alleles (No) and effective alleles (Ne) were 8.88±0.7 and 4.18±0.38 respectively. The average observed heterozygosity (Ho, 0.69±0.04) was less than the expected heterozygosity (He, 0.71±0.03). The f-estimates indicated 4.3% heterozygote deficit in the Purnea population. This obviously signifies that this breed retains considerable intensity of genetic variability and low level of inbreeding, notwithstanding its declining population in the breeding region. Investigation on present status of Purnea population based on physical and molecular characteristics demands its recognition as thirty-fifth breed of indigenous cattle.